(untitled) (Journal of the College of Basic Education, 2022)
This research is directed to those who are interested in literature and issues of literary criticism, and its paths, students and scholars of modern critical curricula.Critical inquiry curricula have witnessed an unparalleled development, thanks to the contributions of humanities and linguistics. Psychological, formative, textual and cultural criticism curricula have opened several areas for commentators of literature characterized by clarity and fertility. This research presents a clear and documented presentation of these trends and teaching methods for students and scholars of criticism. One of these curricula and its rulings and applied fields and potential limits